Re-embroidering the robe : faith, myth and literary creation since 1850 - Bray, S. (Suzanne); Gavin, Adrienne E., 1962-; Merchant, Peter (Cambridge Scholars Pub., 2008)
Religious faith, myths and legends have always been present in literature. However, their role has changed over time. Since the middle of the nineteenth century, with the diminishing role of religion in European society, writers with some kind of belief system, whether religious or political, have tended to use myth in two different ways. They have either retold the old, familiar myths of the past so that they carry fresh messages relevant to a contemporary audience or created their own, new ...